Seismic behavior tests of square reinforced concrete-filled steel tube columns connected to RC beam joints - Gan, Dan (2021)
This paper proposes a joint system that connects the thin-walled square reinforced concrete–filled steel tube (RCFST) column to RC beams at both sides of the joint. In order to delay the local buckling of square steel tubes with high width-to-thickness ratio and enhance confinement effect on infilled concrete, diagonal stiffeners were welded to adjacent sides of the internal square steel tube and longitudinal bars were embedded in the square RCFST columns. Four RCFST joints with internal diaphragms were tested up to a large drift ratio of 6.7% under combined axial compression and reversed cyclic loading. All four specimens were designed according to the strong-column-weak-beam concept, and the strong-joint-weak-member seismic design philosophy. The cross-sectional dimensions of the RCFST column were 300×300  mm. The dimensions of the beam cross section were 200×350  mm and high-strength steel rebars (600 MPa) were adopted in the RC beams. The width-to-thickness ratio of the square joint tube and the level of axial load in the column were two important parameters to be studied. Two types of failure mode, i.e., beam flexural failure and beam flexural failure with bond failure, were observed. Both failure modes were ductile and the joints showed excellent seismic performance under cyclic loading. Based on the test results, some design considerations for the joints were recommended.